1997
DOI: 10.1016/s0022-5223(97)70112-0
|View full text |Cite
|
Sign up to set email alerts
|

The aortic root in supravalvular aortic stenosis: The potential surgical relevance of morphologic findings

Abstract: Our data demonstrate that the entire valvular apparatus is always affected by the so-called supravalvular stenosis. Anatomic restoration of the aortic root should ideally take into account all of the deformed components by enlarging all three sinuses of Valsalva at the sinotubular junction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 25 publications
2
64
0
1
Order By: Relevance
“…16 However, these estimates are likely to be below the true prevalence because the majority of patients in those studies did not have evaluations of the coronary arteries, by either imaging or inspection at surgery. Stamm et al 34 reported a prevalence of coronary ostial stenosis of 45% in their surgical series of patients with SVAS. Ostial stenosis is more frequent in patients with WS and severe vascular disease 41 ; in those patients with stenosis of the thoracic aorta (STA), coronary ostial stenosis had a prevalence of ≈19%.…”
Section: Coronary Artery Abnormalities In Svasmentioning
confidence: 98%
See 2 more Smart Citations
“…16 However, these estimates are likely to be below the true prevalence because the majority of patients in those studies did not have evaluations of the coronary arteries, by either imaging or inspection at surgery. Stamm et al 34 reported a prevalence of coronary ostial stenosis of 45% in their surgical series of patients with SVAS. Ostial stenosis is more frequent in patients with WS and severe vascular disease 41 ; in those patients with stenosis of the thoracic aorta (STA), coronary ostial stenosis had a prevalence of ≈19%.…”
Section: Coronary Artery Abnormalities In Svasmentioning
confidence: 98%
“…12,15,29,30 Two types of SVAS are typically seen in patients with WS: a discrete, hourglass narrowing at the sinotubular junction or a diffuse, long-segment stenosis of the ascending aorta 31 ( Figure 4). The hourglass type of SVAS is the more common of the two, 33,34 occurring in ≈75% of children. 35 The diffuse type of SVAS often is associated with stenoses of the brachiocephalic vessels.…”
Section: Supravalvar Aortic Stenosismentioning
confidence: 99%
See 1 more Smart Citation
“…In a catheterization study of 26 patients with WBS, coronary artery dilation or stenosis was found in 27% (39). In mixed cohorts of individuals who had either WBS or mutations in the ELN gene in conjunction with severe SVAS requiring surgery, coronary disease was found in 28%-45% (49,50). Although coronary disease appears to be related to the severity of supravalvular aortic narrowing (39), case reports indicate that severe coronary artery disease leading to death may be the sole vascular feature in some patients with WBS (51,52).…”
Section: Clinical Features Of Wbsmentioning
confidence: 99%
“…As a result, a characteristic hourglass narrowing of the aorta develops at the sinotubular junction. In approximately 30% of cases, there is diffuse tubular narrowing of the ascending aorta, often extending to the arch and the origin of the brachiocephalic vessels (4).…”
Section: Sporadic Supravalvular Stenosis Inmentioning
confidence: 99%